First-line treatment of patients with HER2-positive metastatic gastric and gastroesophageal junction cancer - Selin Aktürk Esen; Yakup Ergun; Cihan Erol; Rukiye Arikan; Muhammed Muhiddin Er; Muhammed Mustafa Atci; Atakan Topçu; Gökhan Uçar; Baran Akagündüz; Musa Bariş Aykan; Miraç Özen; Naziyet Köse Baytemur; et al. (Biomolecules & Biomedicine, 2022)
Fluoropyrimidine+cisplatin/oxaliplatin+trastuzumab therapy is recommended for the first-line treatment of HER2-positive metastatic gastric adenocarcinoma. However, there is no comprehensive study on which platinum-based treatment should be preferred. This study aimed to compare the treatment response and survival characteristics of patients with HER2-positive metastatic gastric or gastroesophageal junction (GEJ) cancer who received fluorouracil, oxaliplatin, and leucovorin (mFOLFOX)+trastuzumab or cisplatin and fluorouracil (CF)+trastuzumab as first-line therapy. It was a multicenter, retrospective study of the Turkish Oncology Group, which included 243 patients from 21 oncology centers. There were 113 patients in the mFOLFOX+trastuzumab arm and 130 patients in the CF+trastuzumab arm. The median age was 62 years in the mFOLFOX+trastuzumab arm and 61 years in the CF+trastuzumab arm (P = 0.495). 81.4% of patients in the mFOLFOX+trastuzumab arm and 83.1% in the CF+trastuzumab arm had gastric tumor localization (P = 0.735). The median progression-free survival (PFS) was significantly higher in the mFOLFOX+trastuzumab arm (9.4 months vs. 7.3 months, P = 0.024). The median overall survival (OS) was similar in both groups (18.4 months vs. 15.1 months, P = 0.640). Maintenance trastuzumab was continued after chemotherapy in 101 patients. In this subgroup, the median OS was 23.3 months and the median PFS was 13.3 months. In conclusion, mFOLFOX+trastuzumab is similar to CF+trastuzumab in terms of the median OS, but it is more effective in terms of the median PFS in the first-line treatment of HER2-positive metastatic gastric and GEJ cancer. The choice of treatment should be made by considering the prominent toxicity findings of the chemotherapy regimens.